Food demand in Bulgaria over the transition period - Mishev P.; Tzoneva M.; Ivanova N. (Agricultural price reform under transition in Bulgaria, Romania, and Slovenia, 1998)
The objective of this paper is to explain the changes in the consumption of food products observed during the transition period and to estimate price and income elasticities of food demand. The paper uses cross-section household budget survey data for the 1990 - 1994 period. Engel curves are estimated, then with the use of the Frisch parameter of the marginal utility of income complete matrix of price elasticities for five broad consumption groups and for ten food products is established. The results show very low price elasticities and quite high income elasticities of food demand. On the basis of this observation it is deduced that the major factor in the decline of food consumption during transition is the decline in real incomes rather than the increase in food prices.